Kesulitan peserta didik dalam menyelesaikan soal cerita pada kemampuan koneksi matematis: Systematic Literature Review (SLR) - Andini, Windriani Rantiani; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
A  systematic literature review (SLR) of five This study describes the findings of research regarding the analysis of mathematical comprehension abilities in solving word problems using examples of self-efficacy research on mathematics learning difficulties.The people who were indexed by SCOPUS, SINTA, and REPOSITORY between 2018 and 2023 and were located in Indonesia make up the research sample. Google Scholar, Semantic Scholar Eric Journal, Researchgate, and Repository served as sources for these sample data searches. Information assortment was completed by recording all articles connected with understudies' numerical association ability in tackling word issues in light of year of examination, sort of exploration, level of training, research socioeconomics, and diary file. The quantitative and descriptive presentation of all obtained data is used. Using the SLR strategy, it was discovered that the majority of research was distributed in 2018, with SINTA 2 indexing dominating. The island of Java dominated most of this exploration, which was carried out at the junior high school level. Students' difficulties learning mathematics have been the primary focus of research on students' mathematical connection abilities when solving story problems.